Social Theology of the Free Nutritious Meal Program: Reinterpretation of QS. Al-Baqarah: 168 in Tafsir Al-Azhar - Baeti Rohman (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
This study aims to provide a theological reinterpretation of Quranic verse (QS.) Al-Baqarah: 168, shifting its focus from a mere jurisprudential (fiqh) guide for personal consumption toward a foundational framework for political ethics and public policy (siyasah syar'iyyah). The primary objective is to redefine the term thayyiban within the context of the national nutritional emergency (stunting) and the strategic efforts to enhance the nation's cognitive intelligence in pursuit of the